Implementation of Decision Support Systems In Cement Supplier Evaluation Using Fuzzy Analytical Hierarchy Process (F-AHP) - Muhammad Hermansyah (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2021)
The implementation of raw material selection is a multicriteria problem where each criterion used has a different importance and the information about it is not known with certainty. Selection of suppliers based on low price bids is no longer efficient in obtaining maximum performance, SCM must combine other criteria that are relevant to company objectives. PT. X faces obstacles related to unstable supplier performance, including delays, fluctuating prices and delivery that is not in accordance with the orders. The instability that occurs is not yet due to other factors that tend to be far from the company's plans and estimates.This research approach uses the Analytical Hierarchy Process (AHP) in the decision-making support process of a complex and measurable problem uses fuzzy to accommodate the uncertainty that occurs when making decisions. Based on the results of calculations that have been carried out using the Fuzzy AHP combination method and the assessment using the rating scale, the calculation results of each criterion in this study are obtained with the quality criteria of 0.2829, delivery criteria 0.2096, price criteria 0.1457, service criteria 0 , 0984, the criteria for production capability 0.1466, and the criteria for supplier characteristics 0.1172. Based on these calculations, the quality criteria are the top priority in selecting suppliers, especially in the supply of cement raw materials.